2010
DOI: 10.19030/cier.v3i1.163
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Among English Language Teachers In Malaysia

Abstract: The phenomenon of burnout has always been under scrutiny, especially with reference to the teachers and their demographics. This study has deliberately focused on the English teachers’ burnout and its relation with their demographics of age and workload in Malaysia. The findings showed that burnout is evident at high levels in all dimensions. In addition, some age and workload categories demonstrated significant relations with emotional exhaustion, depersonalization and reduced personal accomplishment. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 7 publications
10
33
1
3
Order By: Relevance
“…Unlike previous findings [6,24], this study found that level of teacher burnout for emotional exhaustion and personal accomplishment were moderate meanwhile the level of teacher burnout for depersonalization was low. On the other hand, the results of this study were similar to those of previous studies [17,18,25] that found the level of job satisfaction is moderate.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike previous findings [6,24], this study found that level of teacher burnout for emotional exhaustion and personal accomplishment were moderate meanwhile the level of teacher burnout for depersonalization was low. On the other hand, the results of this study were similar to those of previous studies [17,18,25] that found the level of job satisfaction is moderate.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the study (Mukundan & Khandehroo, 2010) suggested that high levels of burnout are obvious in all three dimensions among English teachers in public schools. In other words, the teachers showed emotional exhaustion, a high level of depersonalization, and reduced personal accomplishment.…”
Section: Review Of Literaturementioning
confidence: 85%
“…Several studies have been conducted in Malaysia to explore teacher burnout (Mukundan & Khandehroo, 2009;Mukundan & Khandehroo, 2010;Mukundan & Ahour, 2011;Jamshidirad, Mukundan, & Nimehchisalem, 2012;. Using the MBI Educators Survey, Mukundan and Khandehroo (2009) looked into Malaysian primary and secondary English teachers' burnout with reference to their gender, teaching experience, and level of education.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In specific, the turnover intention among Malaysian academicians of private higher education institutions (PHEIs) is in critical stage (Hashim & Mahmood, 2011). Various studies had been conducted by the local scholars to identify the causes of the turnover such as job stress (Zakerian & Subramaniam, 2009;Nasrudin, Ramayah, & Beng, 2006), work family conflict (Panatik et al, 2011), job burnout (Mukundan & Khandehroo, 2010) and organizational commitment (Marmaya et al, 2011;Lo, Ramayah, & Min, 2009). …”
Section: Introductionmentioning
confidence: 99%